Mobile Ad-Hoc Network (MANET) Method: Some Trends and Open Issues - Wijonarko, Dwi; Arifin, Samsul; Faisal, Muhammad; Pratama, Muhammad Nabil; Priambodo, Okta Nindita; Nugraha, Edwin Setiawan (MBI, 2025)
This study analyzes the latest developments and trends in the field of Mobile Ad-Hoc Networks (MANET) through a bibliometric approach using a metadata dataset from publications taken from Scopus between 2021 and 2024. By utilizing VOSviewer to visualize the data, the study identified key keywords that dominated the MANET literature, such as